(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Corona virus disease 2019 (COVID-19) is a global pandemic disease caused by novel corona virus called SARS-CoV-2. Over 213 countries as of July 15, 2020, 13.1 million people are affected by this deadly virus. More than 100 million women are pregnant worldwide and potentially all are at risk of exposure to SARS-CoV-2 infection. Coronaviruses cause illness ranging in severity from common cold and severe respiratory illness to death. Frequent manifestations of COVID-19 include fever, cough, myalgia, headache, and diarrhoea. Abnormal test result shows abnormalities on chest radiographic imaging, lymphopenia, leukopenia, and thrombocytopenia. Physiological changes during pregnancy like altered immunity, reduced functional residual volume, pressure on diaphragm by advanced gravid uterus may lead to adverse respiratory outcome in any viral disease. Maternal mortality was very high in other corona viruses like Severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). No evidence of in utero transmission was seen in SARS or MERS. Coronavirus disease 2019 might increase the risk of vertical transmission and pregnancy complications. So, meticulous management is necessary for safe maternal and foetal outcome. Early isolation, aggressive infection control procedures, oxygen therapy are the key component of COVID-19 management. In pregnancy multidisciplinary approach should be taken for general and obstetrical management. At present there is no specific treatment for COVID-19. Based on results from observational studies empiric antibacterial and antiviral drugs are used. Very recently a few controlled trials were published that suggest few treatment options. On the basis of published data and recommendations of international health organizations, the aim of this review is to explore effective treatment and care of the pregnant women throughout pregnancy, during childbirth and afterwards in this novel SARS-CoV-2 crisis. J Bangladesh Coll Phys Surg 2020; 38(0): 91-108